Prognostic factors associated with upper gastrointestinal bleeding based on the French multicenter SANGHRIA trial - Quentin, Vincent; Remy, André-Jean; Macaigne, Gilles; Leblanc-Boubchir, Rachida; Arpurt, Jean-Pierre; Prieto, Marc; Koudougou, Carelle; Tsakiris, Laurent; Grasset, Denis; Vitte, René-Louis; Cuen, David; Verlynde, Juliette; Elriz, Khaldoun; Ripault, Marie-Pierre; Ehrhard, Florent; Baconnier, Mathieu; Herrmann, Sofia; Talbodec, Nathalie; Lam, You-Heng; Bideau, Karine; Costes, Laurent; Skinazi, Florence; Touze, Ivan; Heresbach, Denis; Lahmek, Pierre; Nahon, Stéphane; Members of the Association Nationale des Hépato-gastroentérologues des Hôpitaux Généraux (ANGH) SANGHRIA Study Group; Agnello, Christophe; Alabert, Frédérique; Amil, Morgane; Arondel, Yves; Arotcarena, Ramuntcho; Arpurt, Jean-Pierre; Aziz, Karim; Baconnier, Mathieu; Barge, Sandrine; Barjonet, Georges; Baudon, Julien; Bauguion, Lucile; Bellecoste, Marie; Bellon, Serge; Benezech, Alban; Berete, Aliou; Berger, Chantal; Bertolino, Jean-Guy; Bideau, Karine; Billet, Gaëlle; Bocci, Massimo; Borel, Isabelle; Boualit, Madina; Boutroux, Dominique; Bramli, Slim; Catala, Pascale; Charpignon, Claire; Chelly, Jonathan; Colin, Marie; Combes, Rémi; Costes, Laurent; Coulibaly, Baya; Cuen, David; D'hautefeuille, Gaëlle; Davy, Hortense; De Lustrac, Mercedes; De Montigny-Lenhardt, Stéphanie; Delobel, Jean-Bernard; Dobrin, Anca-Stela; Ehrhard, Florent; El Hajjl, Weam; Elriz, Khaldoun; Esch, Anouk; Faroux, Roger; Fron, Mathilde; Garceau, Cécile; Garioud, Armand; Geagea, Edmond; Grasset, Denis; Guerbau, Loïc; Haque, Jessica; Harnois, Florence; Heluwaert, Frédéric; Heresbach, Denis; Herrmann, Sofia; Horaist, Clémence; Kaassis, Mehdi; Kerneis, Jean; Koudougou, Carelle; Lagin, Ludovic; Laly, Margot; Lam, You-Heng; Leblanc-Boubchir, Rachida; Legruyer, Antonia; Lemee, Delphine; Locher, Christophe; Louvel, Dominique; Lubret, Henri; Macaigne, Gilles; Mace, Vincent; Maillard, Emmanuel; Meszaros, Magdalena; Redha Moussaoui, Mohammed; Nahon, Stéphane; Nobecourt, Amélie; Pateu, Etienne; Paupard, Thierry; Pauwels, Arnaud; Pelaquier, Agnès; Pennec, Olivier; Petiet, Mathilde; Pinard, Fabien; Polin, Vanessa; Prieto, Marc; Quartier, Gilles; Quentin, Vincent; Remy, André-Jean; Ripault, Marie-Pierre; Rosa, Isabelle; Salvati, Thierry; Schnee, Matthieu; Senouci, Leila; Skinazi, Florence; Talbodec, Nathalie; Thiebault, Quentin; Touze, Ivan; Trompette, Marie; Tsakiris, Laurent; Vandamme, Hélène; Vanveuren, Charlotte; Verlynde, Juliette; Vickola, Joseph; Vitte, René-Louis; Wartel, Faustine; Zaharia, Oana; Zanditenas, David; Zavadil, Patrick (Endoscopy International Open, 2021)
Background and study aims Prognostic and risk factors for upper gastrointestinal bleeding (UGIB) might have changed overtime because of the increased use of direct oral anticoagulants and improved gastroenterological care. This study was undertaken to assess the outcomes of UGIB in light of these new determinants by establishing a new national, multicenter cohort 10 years after the first. Methods Consecutive outpatients and inpatients with UGIB symptoms consulting at 46 French general hospitals were prospectively included between November 2017 and October 2018. They were followed for at least for 6 weeks to assess 6-week rebleeding and mortality rates and factors associated with each event.Results Among the 2498 enrolled patients (mean age 68.5 [16.3] years, 67.1 % men), 74.5 % were outpatients and 21 % had cirrhosis. Median Charlson score was 2 (IQR 1–4) and Rockall score was 5 (IQR 3–6). Within 24 hours, 83.4 % of the patients underwent endoscopy. The main causes of bleeding were peptic ulcers (44.9 %) and portal hypertension (18.9 %). The early in-hospital rebleeding rate was 10.5 %. The 6-week mortality rate was 12.5 %. Predictors significantly associated with 6-week mortality were initial transfusion (OR 1.54; 95 %CI 1.04–2.28), Charlson score > 4 (OR 1.80; 95 %CI 1.31–2.48), Rockall score > 5 (OR 1.98; 95 %CI 1.39–2.80), being an inpatient (OR 2.45; 95 %CI 1.76–3.41) and rebleeding (OR 2.6; 95 %CI 1.85–3.64). Anticoagulant therapy was not associated with dreaded outcomes.Conclusions The 6-week mortality rate remained high after UGIB, especially for inpatients. Predictors of mortality underlined the weight of comorbidities on outcomes.